Mental simulation and meaning in life. [article]. - Waytz, Adam.; Hershfield, Hal E.; Tamir, Diana I.
Mental simulation, the process of self-projection into alternate temporal, spatial, social, or hypothetical realities is a distinctively human capacity. Numerous lines of research also suggest that the tendency for mental simulation is associated with enhanced meaning. The present research tests this association specifically examining the relationship between two forms of simulation (temporal and spatial) and meaning in life. Study 1 uses neuroimaging and demonstrate that enhanced connectivity in the medical temporal lobe network, a subnetwork of the brain?s default network implicated in prospection and retrospection, correlates with self-reported meaning in life. Study 2 demonstrates that experimentally inducing people to think about the past of future versus the present enhances self-reported meaning in life, through the generation of more meaningful events. Study 3 demonstrates that experimentally inducing people to think specifically versus the general about the past or future enhances self-reported meaning in life. Study 4 turns to spatial simulation to demonstrate the experimentally inducing people to think specifically about an alternate spatial location (from the present location) increases meaning derived from this simulation compared to thinking generally about another location or specifically about one?s present location. Study 5 demonstrates that experimentally inducing people to think about an alternate spatial location versus one?s present location enhances meaning in life, through meaning derived from this simulation. Study 6 demonstrates that simply asking people to imagine completing a measure of meaning in life in an alternate location compared with asking them to do so in their present location enhances reports of meaning. This research sheds lights on an important determinant of meaning in life and suggests that undirected mental simulation benefits psychological well-being. - - (from the authors)
Keywords: Self-projection-Periodicals.; Mental simulation-Periodicals.; Meaning in life-Periodicals.; Mental time travel-Periodicals.